Guinea-Bissau : Staff Report for the 2015 Article IV Consultation and Request for a Three-Year Arrangement Under the Extended Credit Facility. (IMF Staff Country Reports; Country Report ;, 2015)
EXECUTIVE SUMMARY Context: A series of coups d'etat since independence have resulted in chronic political instability and deterred economic and social progress. Guinea-Bissau has re-initiated progress since the assumption of office of the current inclusive government in mid-2014. The economy is now recovering after a decline in 2012 and marginal growth in 2013. Inflation remains low, and socio-political stability seems achievable. The coup d'etat of April 2012 stalled implementation of the three-year Extended Credit Facility (ECF)- supported program approved by the Board in May 2010, and the arrangement lapsed subsequently. The Fund's support under the Rapid Credit Facility (RCF) disbursement of 2014 and the authorities' commitment to reforms have re-ignited donor confidence. Article IV Discussions. Policy discussions focused on measures to overcome fragility; fiscal consolidation and public financial management reforms; restoring financial stability; borrowing policies and long-term debt sustainability; private sector development and structural reforms to enhance inclusive growth prospects. The Proposed Program. The authorities' development program, anchored on the Strategic Plan for 2014-18, aims to consolidate the fiscal position through better expenditure management and enhanced revenue mobilization, deepen institutional reform, mitigate vulnerabilities, and develop the private sector to support growth and employment. The program focuses on improving the policy framework by addressing governance and security issues, strengthening budgetary transparency as well as public investment and debt management, and improving compilation of statistics. Structural benchmarks focus on these issues while QPCs include a floor on revenues collection and a ceiling on net credit to government (the anchor of the program). Request for an Extended Credit Facility Arrangement. To support their medium-term economic reform program, the authorities request a three-year arrangement under the ECF in an amount equivalent to SDR 17.04 million (120 percent of quota). Risks to the program include the still fragile political situation, which could delay implementation of reforms, adverse terms of trade developments, and weakening donor confidence, and the heightened risk of incursion of the Ebola virus from neighboring countries.